Crisis and Recovery in the Pearl River Delta. Growth and Employment in the Electronics Industry - Ohm, Stefan; Liefner, Ingo (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
Compared with most other regions and industries in China, the electronics industry in the Pearl River Delta (PRD) has been hit hard by the crisis of 2008 and 2009. Numerous companies have ceased operations and thousands of workers have been laid off. The orientation of the electronics industry towards exporting low-cost products has proven to be a point of weakness in this ongoing crisis. The aims of this article are threefold: firstly, to highlight the key reasons for the crisis and the Pearl River Delta’s susceptibility to it; secondly, to analyse the channels through which the global crisis affected the PRD, and thirdly, to analyse the immediate effects on companies. All analyses are based on firm-level data acquired in 2009 with support from DFG SPP 1233. They show that the crisis has mainly affected the internationally oriented companies in the PRD.